1999
DOI: 10.1023/a:1008323604269
|View full text |Cite
|
Sign up to set email alerts
|

Weekly gemcitabine and cisplatin in advanced non-small-cell lung cancer: A phase II study

Abstract: This regimen appears to be active and to have a favourable toxicity profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Given the good tolerability and the efficacy of a weekly gemcitabine and cisplatin regimen that we employed in patients aged 65 years or less [3], we planned to evaluate the same drug schedule in patients aged 70 years or more.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the good tolerability and the efficacy of a weekly gemcitabine and cisplatin regimen that we employed in patients aged 65 years or less [3], we planned to evaluate the same drug schedule in patients aged 70 years or more.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous trial we observed partial responses in 12 out of the 30 evaluable patients (40%, with 95% CI 22.5–57.5%) [3]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this schedule may facilitate the synergistic interaction between gemcitabine and cisplatin. A number of trials of 28-day regimens report frequent dose modifications and omissions, particularly on day 15 in bladder and lung cancer (13,20,21). Optimising the delivered dose while minimizing dose delays and dose modifications due to toxicity are likely to have an impact on disease-free and overall survival (18).…”
Section: Discussionmentioning
confidence: 99%
“…In all these tumour types, including NSCLC, further improvement of therapy with cisplatin has been extensively investigated. Cisplatin has been used in combinations with other different chemotherapeutic agents, such as DNA-alkylators, topoisomerase II inhibitors, vinorelbine and gemcitabine (Fukuoka et al, 1992;Liu, 1993;Sculier et al, 1994;Gridelli et al, 1996;Wozniak et al, 1998;Lippe et al, 1999). Besides evaluation of different combinations of cisplatin, important other approaches have focused on increasing the dose and/or the dose intensity of the drug using higher doses per course (Klastersky et al, 1986;Gandara et al, 1993), or shortening the treatment interval (Planting et al, 1993(Planting et al, , 1994(Planting et al, , 1995a(Planting et al, , b, 1996a(Planting et al, , b, 1997(Planting et al, , 1999.…”
mentioning
confidence: 99%